Perspectives and potential applications of endophytic microorganisms in cultivation of medicinal and aromatic plants - Tripathi, Arpita; Pandey, Praveen; Tripathi, Shakti Nath; Kalra, Alok (Frontiers in Plant Science, 2022)
Ensuring food and nutritional security, it is crucial to use chemicals in agriculture to boost yields and protect the crops against biotic and abiotic perturbations. Conversely, excessive use of chemicals has led to many deleterious effects on the environment like pollution of soil, water, and air, loss of soil fertility, development of pest resistance and now is posing serious threats to biodiversity. Therefore, farming systems need to be upgraded towards the use of biological agents for retaining agricultural and environmental sustainability. Plants exhibit a huge and varied niche for endophytic microorganisms inside the planta resulting in a closer association between them. Endophytic microorganisms play a vital role in plant physiological and morphological characteristics including growth promotion, survival and fitness. Their mechanism of action includes both direct/indirect such as mineral phosphate solubilisation, fixating nitrogen, synthesis of auxins, production of siderophore and various phytohormones. Medicinal and aromatic plants (MAPs) hold a crucial position worldwide for their valued essential oils and several phytopharmaceutically important bioactive compounds since ancient times; conversely, owing to the high demand for natural products, commercial cultivation of MAPs is on the upswing. Further, the vulnerability to various pests and diseases enforces noteworthy production restraints that affect both crop yield and quality. Efforts have been made towards enhancing yields of plant crude drugs by improving crop varieties, cell cultures, transgenic plants, etc, but these are highly cost-demanding and time-consuming measures. Thus, it is essential to evolve efficient, eco-friendly, cost-effective simpler approaches for improvement in yield and health of the plants. Harnessing endophytic microorganisms as biostimulants can be an effective and alternative step. This review summarizes the concept of endophytes, their multidimensional interaction inside the host plant and the salient benefits associated with endophytic microorganisms in medicinal and aromatic plants.